The Influence of e-WoM, Marketplace Advertising, and FoMO on Purchase Decision for Sendy Leather on Shopee, Mediated by Trust - Rahmatullah, Rafi Rasyad; Hermeindito, Hermeindito (Journal of Social Commerce, 2025)
This study investigates the influence of electronic word of mouth (e-WoM), marketplace advertising, and fear of missing out (FoMO) on consumer purchase decisions for Sendy Leather products on Shopee, with trust as a mediating variable. The research employs a quantitative approach using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) and is supported by 209 purposively selected respondents who have purchased Sendy Leather through Shopee. Findings reveal that e-WoM and FoMO positively and significantly affect trust, while marketplace ads do not. In turn, e-WoM, FoMO, and marketplace ads directly impact purchase decisions, with trust acting as a significant mediator between e-WoM and FoMO toward purchasing behavior. The study concludes that trust and psychological urgency shape digital consumer behavior, emphasizing the need for personalized and credible digital marketing strategies. This research offers managerial implications for local brands operating in competitive online marketplaces.